Potential methods for heart rate monitoring during neonatal resuscitation in the delivery room - Sidahmed, Shiemaa Sidhmed Awad (2020)
This thesis aims to investigate the use of dry and capacitive ECG sensors for newborns’ heart rate monitoring in the delivery room. The main limitations of the standard wet ECG sensors for this application are the need for skin preparation and possible skin scarring caused by the conductive gel.